2018
DOI: 10.1111/cen.13800
|View full text |Cite
|
Sign up to set email alerts
|

High Irisin levels in nondiabetic HIV‐infected males are associated with insulin resistance, nonalcoholic fatty liver disease, and subclinical atherosclerosis

Abstract: In male HIV patients without diabetes, higher irisin concentrations are positively associated with insulin resistance, NAFLD and subclinical atherosclerosis. However, waist-hip-ratio is the main determinant of insulin resistance, and PAI-1 and lipodystrophy were the strongest determinants of IMT in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…Given the fact that treatment with exogenous irisin ameliorated hepatic I/R injury, the early increase in irisin may be an endogenous protective mechanism for I/R injury, which exhausted at later stages. Interestingly, recent studies found that high irisin levels were positively related to insulin resistance, nonalcoholic fatty liver disease, subclinical atherosclerosis and associated with more severe NAFLD [29] , [30] . However, increasing evidence has shown that irisin increases energy expenditure, improves insulin resistance, reduces hyperlipidemia and hyperglycemia, inhibits hepatic cholesterol synthesis, and ameliorates atherosclerosis [11] , [23] , [31] , [32] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the fact that treatment with exogenous irisin ameliorated hepatic I/R injury, the early increase in irisin may be an endogenous protective mechanism for I/R injury, which exhausted at later stages. Interestingly, recent studies found that high irisin levels were positively related to insulin resistance, nonalcoholic fatty liver disease, subclinical atherosclerosis and associated with more severe NAFLD [29] , [30] . However, increasing evidence has shown that irisin increases energy expenditure, improves insulin resistance, reduces hyperlipidemia and hyperglycemia, inhibits hepatic cholesterol synthesis, and ameliorates atherosclerosis [11] , [23] , [31] , [32] .…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing evidence has shown that irisin increases energy expenditure, improves insulin resistance, reduces hyperlipidemia and hyperglycemia, inhibits hepatic cholesterol synthesis, and ameliorates atherosclerosis [11] , [23] , [31] , [32] . The increased release of irisin under such conditions could reflect a response to deterioration or a compensatory increase to overcome an underlying insulin resistance, nonalcoholic fatty liver disease or subclinical atherosclerosis [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found a weak but significant positive association of circulating irisin with insulin resistance in non-diabetic subjects, 24 fasting blood glucose has been generally positively associated with irisin levels, 14 but acute changes in glucose or insulin levels, as during an OGTT, do not affect irisin levels. Ethnic variability might affect the association, since insulin sensitivity indices show an inverse association with irisin in non-diabetic people of Asiatic and American origin, 24 , 25 but a positive association was reported in a European study. 26 The present results showed the negative association between irisin level and insulin sensitivity indices in both non-diabetes subgroup and the whole study cohort, which was also supported by its positive association with insulin resistance as assessed by the insulin resistance index, these results were in accordance with the previous study in a non-diabetes population.…”
Section: Discussionmentioning
confidence: 85%
“…As early as 2014, in a study of 192 European ancestry healthy people, it was found that irisin was positively correlated with the subjects’ carotid artery IMT ( 60 ). Moreover, a 25-year cohort study by Kwaniewska M ( 61 ) and a cross-sectional study of men with HIV infection ( 62 ) supported this result. In this regard, they explained that irisin may indirectly participate in the formation of atherosclerosis through fat or insulin ( 60 , 62 ).…”
Section: Irisin In Atherosclerosismentioning
confidence: 85%
“…As in non-obese subject, the serum irisin is mainly derived from muscle, while in the obese subject the proportion of fat source increases ( 63 ). Similar to the degrees of obesity, Moreno found that the high value of plasminogen activator inhibitor-1 (PAI-1) at baseline could also have a significant impact on the results, which could even count as an independent biomarker related to the thickness of the carotid artery IMT in patients ( 62 ). In a study based on a Japanese male population ( 64 ), the authors found that if cardiometabolic risk factors are taken into account, irisin had nothing to do with the prevalence of coronary artery calcification, but was related to progression.…”
Section: Irisin In Atherosclerosismentioning
confidence: 99%